The efficacy of local gentamicin-collagen sponge in prevention of infection following open fracture of femur - Kularaj Subramaniam
Open fractures are known as a major predisposing factor for a higher incidence of infection. The aim of this study is to assess the efficacy of the antibiotic impregnated collagen sponge in reducing the risk of infection in open fractures Grade 3. Observational cohort study, evaluating incidence of infection in open fractures of the femur Grade 3A following insertion of gentamicin impregnated collagen sponge (Collatamp®) during definitive fracture fixation. ESR and TWC were used as blood parameters to observe for possibility of infection from pre-operatively up to follow up visits at clinic. A total number of 36 patients, whom had sustained open fracture of the femur Grade 3A, underwent internal fixation with antibiotic impregnated collagen sponge insertion. Overall ESR and TWC in both male and female gender were down going trend, with P values <0.001. The data analysis shows that there was no infection identified in 97.2% of patients, following the internal fixation and antibiotic impregnated collagen sponge insertion. There was only 1 patient (2.8%) who had developed infection following the definitive internal fixation and antibiotics impregnated collagen sponge insertion. The use of antibiotic impregnated collagen sponge in open fractures was effective in reducing the risk infection. Furthermore, this allows for an uncomplicated union of the bone following definitive fixation.